Application of the House of Risk for Operational Risk Mitigation in Regional Public Water Utilities - Yogaswara, Komang Bagas Ary; Korry, Putu Dyah Permata (LifeSciFi, 2025)
Clean water is a fundamental public service, and rising customer demand often coincides with increasing operational disturbances at water treatment plants. Current risk management practices remain reactive and are not yet fully aligned with ISO 31000:2018, with no structured method to map relationships between risk events and their causes or to prioritize preventive actions based on effectiveness and implementation difficulty. This study aims to systematically identify, analyze, and mitigate water treatment plant operational risks using the house of risk framework integrated with ISO 31000:2018. A qualitative case study was through in-depth interviews and field observations supported by triangulation. HOR Phase I applied aggregate risk potential analysis to rank risk agents, while Phase II used effectiveness-to-difficulty ratios to prioritize mitigation measures. The study identified fourteen risk events and twelve risk agents, with key contributors including inadequate maintenance scheduling, river landslides or floods, and distribution pipe leakage. Ten mitigation actions were proposed, such as pump performance monitoring, development of technical SOPs, network inspection and flushing, technical training, coordination with dam operators, provision of PPE, and safety enforcement.